Distribution of pressure on the breast in mammography using flexible and rigid compression plates: implications on patient handling. (December 2021) - Dustler, Magnus; Förnvik, Daniel; Timberg, Pontus; Zackrisson, Sophia; Muller, Serge
Background: Breast compression in mammography is important but is a source of discomfort and has been linked to screening non-attendance. Reducing compression has little effect on breast thickness, and likely little effect on image quality, due to force being absorbed in the stiff juxta thoracic area instead of in the central breast. Purpose: To investigate whether a flexible compression plate can redistribute force to the central breast and whether this affects perceived pain. Material and Methods: Twenty-eight women recalled from mammography screening were compressed with flexible and rigid plates while retaining force and positioning, 15 in the craniocaudal (CC) view and 13 in the mediolateral oblique (MLO) view. Pressure distribution was continuously measured using pressure sensors. Results: The flexible plate showed greater mean breast pressure in both views: 2.8 versus 2.3 kPa for CC (confidence interval [CI] = 0.2–0.8) and 1.0 versus 0.5 kPa for MLO (CI = 0.2–0.6). The percentage of applied force distributed to the breast was significantly higher with the flexible plate, both on CC (36% vs. 22%, CI = 1–11) and MLO (30% vs. 14%, CI = 4–13). Conclusion: The flexible plate redistributes pressure to the central breast, achieving a better compression, particularly in the MLO view, though much applied force is still applied to the juxta thoracic region.